Student voices in studies on curriculum decolonisation: A scoping review - Maine, Kenneth; Wagner, Claire (PINS-Psychology in Society, 2021)
With the decolonisation and #feesmustfall movements in higher education going mainstream it is essential that the voices of students continue to be heard and that they occupy a prominent role in the decolonial project. Additionally, it is crucial to understand how their voices have been portrayed, analysed, and framed within scholarly work. This paper presents a scoping review of literature on the voices of students about the decolonisation of the social sciences that may inform the transformation of the research in psychology curriculum. Of the reviewed literature, only 12 articles were identified as relevant, and these generated four themes: complex reactions towards decolonisation, decolonial content, and ways of teaching; the importance of critical engagement and reflections on decolonisation; challenges with disrupting whiteness within higher education; and demographic change at universities. The findings revealed useful insights that could assist in guiding conversations with students about decolonising psychology in the classroom, such as creating safe spaces where students feel comfortable taking social and psychological risks when expressing their uniqueness. Published work on students and academics co-creating a transformed curriculum is lacking, and further studies on decolonisation in higher education in the global South are needed.